Training for Interreligious Classroom Teaching: An Empirical Study - Kienstra, Natascha (Religious education, 2019)
Interreligious education should support cultural and religious diversity in the classroom by inviting new perspectives. Four contexts are important in this regard, as follows: auto-interpretation of one's own religious tradition, auto-interpretation of foreign traditions, allo-interpretation of one's own religious tradition, and allo-interpretation of foreign traditions. Previous empirical research in the Netherlands has indicated that interreligious learning is not possible in the classroom. However, this study investigated interreligious education from the teaching perspective by conducting an exercise among twenty-four religious and worldview teachers. Specifically, a combination of student teachers, schoolteachers, and teacher trainers took part in a secondary school workshop before answering interview questions. Most participants discussed their own or foreign traditions using auto-interpretation. However, approximately half of all teacher trainers discussed their own traditions using allo-interpretation, although none discussed foreign traditions from the same perspective. In addition, student teachers reached the highest level of interreligious learning available in this study by using multiple perspectives to promote inquiry and engage in productive debate. Although interreligious education is problematic at multiple teaching levels, these results indicate that interreligious teaching practices may be improved through increased training.